Metabolomic and proteomic profiling of Spring Lady peach fruit with contrasting woolliness phenotype reveals carbon oxidative processes and proteome reconfiguration in chilling-injured fruit - Monti, Laura Lucia (2019)
Fleshy fruit are susceptible to develop chilling injury (CI) disorders when stored at low temperatures for extended periods during the postharvest. In peach (Prunus persica L. Batsch) fruit, the woolly texture, expressed as a lack of juiciness, is the most important CI symptom. In the present work, we set up to study the metabolomic and proteomic differences of Spring Lady peach fruit, which, despite had been subjected to the same postharvest treatment (24 d at 0 °C followed by 5 d at 20 °C), display a contrasting woolliness phenotype. A drastic decrease in the content of sugars and sugar alcohols (sucrose, fructose, glucose, ribose, xylose, galactose, sorbitol and raffinose), as well as in all the amino acids detected (Ala, Asn, Gly, Glu, Ile, Ser, Thr, and Val), was found in woolly (WF) when compared to juicy fruit (JF). The quantitative proteomic analysis of JF and WF identified 227 differentially expressed proteins (DEP), from which 165 were increased and 62 decreased in WF with respect to JF. The identification of clusters of functionally associated proteins among the DEP revealed biochemical and physiological processes linked to the development of the woolly phenotype; such as sugar catabolism, amino acid usage, and proteome reconfiguration. On the other hand, a decrease of proteins involved in reactive oxygen species (ROS) detoxification, lower ascorbate peroxidase activity, and higher ROS levels, were found in the mesocarp of WF when compared to JF. Overall, this work identifies the induction of carbon oxidation processes, proteome reconfiguration, and increased ROS generation, as relevant metabolic signatures of woolliness development in peach fruit. Besides, the experimental approach used here clearly shows that the woolly phenotype can be triggered in similar biochemical contexts. The relevance of oxidative stress, probably as a consequence of an imbalance between ROS production and elimination, is highlighted as a causal mechanism of woolliness development in peach fruit.